ผลของปริมาณบิสมัทต่อสมบัติทางกลและพฤติกรรมการหดตัวของทองแดงผสมที่ไม่เจือตะกั่ว - นันทวัฒน์ โชคชัยฐานนันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The WHO (World Health OrganizationX water quality standard for lead dissolution has been established to be less than or equal to 0.01 mg per one liter of water. The finding shows two countermeasures that can solve the dissolution issued. The first method is to remove lead near surface using surface treatment technology and the second method is to replace that lead with other elements among which the most commonly is used bismuth. That is a main point of this research; two types of alloys are employed for testing. The first type is Cu-4.5% Sn-7% Zn alloy ingot which is prepared with bismuth added into the alloy with 0.5, 1.0. 2.0 3.0, 5.0 and 7.5% Bi. This process is done in order to investigate the effect of bismuth content, rather wider range for considering water supply and bearing usages, on shrinkage behavior and mechanical properties. Another type is that commercially available lead free alloys in Japan. The specimens are melted in induction furnace of 50 kg capacity at 1250 ℃. After deoxidation of 0.2% of 15% P-Cu alloy, the molten metal is poured at 1150 ℃ into 4 types of mold (JIS H 5120 type A, JIS 5120 type E, Tatur mold and 30 millimeter diameter 100 mm in length cylinder) The result shows that the Mechanical properties exceeded over the requirement of JIS CAC406 Standard are obtain when bismuth content is less than 2.5%. Increasing bismuth content yields the reduction of pipe volume while the porosity and machinability are increased.